The Serum Concentration of Anti-Aging Proteins, Sirtuin1 and αKlotho in Patients with End-Stage Kidney Disease on Maintenance Hemodialysis - Zbroch E; Bazyluk A; Malyszko J; Koc-Zorawska E; Rydzewska-Rosolowska A; Kakareko K; Hryszko T (Clinical Interventions in Aging, 2020)
Edyta Zbroch, 1 Angelika Bazyluk, 1 Jolanta Malyszko, 2 Ewa Koc-Zorawska, 1 Alicja Rydzewska-Rosolowska, 1 Katarzyna Kakareko, 1 Tomasz Hryszko 1 1 2-nd Department of Nephrology and Hypertension with Dialysis Centre, Medical University, Bialystok, Poland; 2Department of Nephrology, Dialysis and Internal Medicine, Medical University of Warsaw, Warsaw, PolandCorrespondence: Edyta Zbroch 2-nd Department of Nephrology and Hypertension with Dialysis Unit, Medical University, Sklodowskiej Curie 24a, Bialystok 15-276, PolandTel +48 85 8317872 Email edzbroch@poczta.onet.plIntroduction: Sirtuin1 (SIRT1) acts as an anti-aging protein due to anti-apoptotic, anti-oxidative and anti-inflammatory effect and is implicated in several diseases including diabetes or cardiovascular problems. SIRT1 renal overexpression indicates oxidative stress. Similarly, αKlotho was primarily exposed as anti-aging factor. It is primary produced in kidney. It’s deficiency is associated with progression of chronic kidney disease and heart disorders.Purpose: The aim of the study was to assess the serum concentration of sirtuin1 and αKlotho in hemodialysis (HD) patients compared to healthy volunteers in regard to age, blood pressure control, residual kidney function (RKF), diabetes, cardiovascular disease, dialysis vintage and type of dialyzer.Patients and Methods: The serum level of SIRT1 and αKlotho was evaluated using ELISA tests in 103 HD patients, median age 67 years and in 21 volunteers. Blood pressure, RRF, echocardiography and dialysis parameters were assessed. HD group was divided according to the presence/absence of RKF.Results: The serum SIRT1 level was higher (28.4 vs 2.71ng/mL, p< 0.0001) and αKlotho was lower (433.9 vs 756.6pg/mL, p< 0.0001) in HD then in control group. αKlotho was lower in those without RKF (387.2 vs 486.2pg/mL, p=0.028). SIRT1 positively correlated with hemodialysis vintage. αKlotho negatively correlated with left ventricular posterior wall thickness. There was no significant relationship between SIRT1 and αKlotho level and age, blood pressure control, type of dialyzer, Kt/V and diabetes. Multivariate analysis revealed association of SIRT1 with ejection fraction (B − 0.72; p=0.32).Conclusion: Elevated SIRT1 and lower αKlotho concentration are associated with impaired kidney function. The decrease in levels of αKlotho may also indicate heart hypertrophy in hemodialysis patients. The role of anti-aging proteins, particularly SIRT1 as biomarkers/predictors of oxidative stress, inflammation and cardiovascular diseases need further examination.Keywords: sirtuin1, αKlotho, chronic kidney disease, hemodialysis